Development of Achievement Motivation Instruments in High School Students - Gitta Citra Wedhayanti; Ni Ketut Suarni; Nyoman Dantes (Bisma The Journal of Counseling, 2020)
This study aims to describe the development of the Achievement Motivation in high school students. This research uses the Research & Development (R&D) method by using the 4D (four-D) model, define, design, develop, & disseminate. But in this study it was modified to 3D, which is define, design, and disseminate. Analysis of instrument validity using the formula CVR and CVI. Reliability test uses the Cronbach Alpha Formula. Based on the analysis it is known that there are 3 items that have a CVR value of 0.60 which are declared valid but need to be revised, and 57 items are declared valid. The instrument validity test results showed that CVI = 0.98 was declared special and the reliability of this instrument was 0.904 with a very high category.